Catalytic Oxidative Dehydrogenation of Light Alkanes over Oxygen Functionalized Hexagonal Boron Nitride. Issue 1 (5th January 2022) - Kumar, Sonu; Lyalin, Andrey; Huang, Zhenguo; Taketsugu, Tetsuya
Abstract: The catalytic activity of oxygen functionalized hexagonal boron nitride (h‐BN) with >B−O−O−B< and >B−O−B< active sites at the zigzag edges for oxidative dehydrogenation (ODH) of light alkanes, specifically ethane (C2 H6 ), propane (C3 H8 ), butane (C4 H10 ), and isobutane (HC(CH3 )3 ) is explored. It has been found that the reaction pathway involves two H atom transfer steps with small activation energies. We demonstrate that the synergy of two active sites, >B−O−O−B< and >B−O−B<, is crucial for the first and second H‐transfer, respectively. With the increase in molecular mass of the considered light alkanes, the ODH reaction temperature decreases. In the case of butane and isobutane, the ODH reaction occurs almost at the same temperature indicating that the reaction is independent of the shape of the isomer. The rate‐limiting nature of the first H‐transfer step is predicted. The charge redistribution during H‐transfers and localized oxygen atomic states in the conduction band are explored to suggest possible descriptors for the rational design of new catalysts. The universal action of the >B−O−O−B< and >B−O−B< active sites for ODH of the light alkanes paves the way for metal‐free BN‐based materials for future catalytic applications. Abstract : The B−O−O−B< and >B−O−B< sites successfully explain the oxidative dehydrogenation of light alkanes. Two key descriptors: 1) different charge of oxygen atoms in the two sites, 2) empty oxygen states at the conduction band, are crucial for the C−H activation.